REQUIREMENT OR NECESSITY: SYSTEMATIC LITERATURE REVIEW ON PARENTAL CONSENT IN COUNSELING FOR MINORS - Novianti Novianti; Nandang Budiman; Nadia Aulia Nadhirah (QUANTA: Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2023)
Children under the age of 18 years or minors are considered unable to make rational decisions so they need parental consent before getting counseling. However, parental consent can be a reason for children to withdraw from getting counseling assistance even though the problem is urgent. Therefore, this research was conducted to review the urgency of parental consent in the implementation of counseling for minors. This study uses the systematic literature review (SLR) method which aims to synthesize and present more in-depth data from 21 selected previous studies in the form of journal articles and books on Google Scholar, PubMed, Harzing, and Mendeley. The urgency of parental consent before counseling for minors is a requirement, not a necessity, which means it is only to determine whether the counseling can be held and does not have a significant impact on the implementation of counseling. Therefore, counselors still have to prioritize the rights and beliefs of children in counseling. Limitations of decisions that can be made by minors without parental intervention need to be examined more deeply in future studies.